PENGARUH PENGENDALIAN INTERNAL, ASIMETRI INFORMASI, MORALITAS APARAT PEMERINTAH DAN KETAATAN ATURAN TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Kasus Pada SKPD Kab. Indragiri Hilir) - Ichsan Randiza; Kamaliah '; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this study was to determine the effect of internal control, information assimetry, morality, and observance of the rules of the tendency of cheating (fraud) accounting at SKPD Indragiri Hilir. This research is a quantitative research with empirical studies. Criteria respondents used in this research that is head and sub staff in the finance department of each regional work units (SKPD) which acts on the part related to the study variables. The samples are 87 respondents. Methods of data collection is done with a question consisting of five instruments using a Likert scale. Of the 87 question have been distributed, the number of question returned as much as 81 question and can be analyzed. The data analysis technique used is quality test data consisting of validity and reliability test, test the classical assumption of normality test, multicolinearity test, and test heterosketastisitas, and hypothesis testing consisting of multiple regression test, the coeficient determination, t test. The results showed that (1) internal controls effect the tendency o fraud accounting (2) the information assimmetry effect the tendency of fraud accounting, (3) the morality of government officials influence the tendency of fraud accounting (4) obedience rules affect the tendency of accounting and (5) internal control, information assimmetry, morality government and observance of rules effect the tendency of fraud accountingKeywords : internal, information, morality, government, accounting.